Tindak Tutur Asertif dalam Kanal Youtube Maudy Ayunda Edisi Booklist (International Forum of Researchers and Lecturers, 2026)
Curiosity is a very important capital to start learning. Because, with curiosity, humans can dig up interesting information and tips so that they can gain broader insight. In this sophisticated era, it is easier for people to find the information they need. One media that is often used to access information is YouTube. There are many videos on YouTube that can provide interesting and quality information, one of which is Maudy Ayunda's video. This research aims to describe the forms of assertive speech acts contained in the booklist edition of Maudy Ayunda's YouTube channel. The approach used in this research is methodological and theoretical. The approach used in this research is a qualitative descriptive approach and a pragmatic approach. The data collection method used in this research was the observation method, followed by the observation technique. The data analysis method in this research is the pragmatic subtype. The research results found that there were types of assertive speech acts including, namely, assertive speech acts stating 31 data, suggesting 11 data, boasting that no data was found, complaining about 5 data, and claiming 14 data.